The Concept of Public Ownership in Sharia Economic Perspective - Anwar, Saiful; Muhlisin, Sofian; Hakiem, Hilman (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
Islam maintains the concept of balance so that wealth is widely distributed and not monopolized by some groups. However, the problem is that many do not understand how Islam views ownership. Ownership in Islam is a person's bond with property rights legalized by Sharia. Ownership is divided into three types, the first is individual ownership, the second is public ownership, and the third is state ownership. This study aims to find out how the concept of public ownership in the perspective of Islamic economics. Forms of public ownership and management of public ownership. The method used by the author in this study is library research based on the formulation of the problem supported by data and data sources from the literature review. Based on the results of research on the concept of public ownership in Islamic economics. Public ownership is a sharia permit for the community to jointly utilize a wealth in the form of goods that are necessary for humans in their daily life which are divided into three groups, namely as public facilities, unlimited mining goods and natural resources whose nature of formation prevents them from being owned only by individuals as individuals. Common property management rights (milkiyah amah) exist in society in general, which is implemented by the state because the state is the representative of the people. The state must manage public property in a professional and efficient manner. Although the State has the right to administer public property, it may not grant that right to specific individuals. Public ownership must provide maximum benefits to the wider community.